Polyamines and salt stress response and tolerance in Arabidopsis thaliana flowers - Tassoni, Annalisa (Plant physiology and biochemistry : PPB, 2008)
In the present study we analysed polyamine metabolism in Arabidopsis thaliana (ecotype Columbia) flowers and stalks collected from plants germinated and grown under increasing salt-stress conditions (0-75 mM NaCl). The expression level of the different isoforms of polyamine biosynthetic enzymes was analysed by reverse transcriptase-polymerase chain reaction (RT-PCR). Spermidine synthase enzyme activity determined both in supernatant and pellet fractions, together with RT-PCR results, led us to hypothesize a different intracellular compartmentation of the isoforms of these enzymes. Free and conjugated polyamines (perchloric acid-soluble and -insoluble) were measured. Free spermidine was the most abundant polyamine and its levels, such as those of free spermine, increased with salt concentration, supporting the hypothesis for a specific role of those polyamines in the response and tolerance to salt stress of Arabidopsis thaliana flowers